The role of teachers in projects - Hattum-Janssen, Natascha van (2012)
The role of teachers changes with the implementation of project approaches. Teachers serve not only as lecturers, but also as tutors or as a coordinator of a project semester. How these roles are different from the teacher as a lecturer and how teachers can prepare for their new roles are the central themes of this chapter. It starts with an overview on project approaches in engineering education and continues with an outline of the project approach as implemented at the Industrial Management and Engineering (IME) degree programme of the University of Minho, Portugal. It furthermore discusses the preparation of teachers for their new roles in projects.